Kajian Teknis Sistem Penerisan Tambang Di Front 2 TB 2.2 Tempilang Bangka Mitra PT Timah (Persero) Tbk: The Technical Study of Mine Drainage System In Front 2 TB 2.2 Tempilang Large Mine of West Bangka PT Timah (Persero) Tbk’S Partner - Yuana, Ines; Tono, E.P.S.B Taman; Pitulima, Janiar (MINERAL, 2016)
Tin ore mining activities in Front 2 of 2.2 Tempilang Large Mine was operated by business partnerof PT Timah (Persero) Tbk, PT Bahtera Sarindo Utama used Open Pit Mining Method with mechanicalsystems. Open Pit Mining Method would eventually form a large basin, so that would become a placefor air accumulation at the base of mine site, applied drainage system used Repressive KuruativeDrainage System by allowing water to pour into the mine and then concentrated on the front sump andthey would be removed from the mine using pumping systems. Rainfall data used included amaximum rainfall data with period of 2005-2014, the calculation of rainfall plans used Gumbeldistribution and calculation of rainfall intensity with Mononobe Equation, but for the period of rain istaken with the 2-year period. From the research, the existing sump had capability to retain water with avolume of 79.5 m3 and existing pumps had the capacity of 86.4 m3/h, while the total water poured inthe mine was 2172.588 m3/day with total of catchman area was 64085.442 m2. To improve drainagesystem performance on Front 2 of 2.2 Tempilang Large Mine, dimensional sump need to be repairedwith a capacity of 1267.336 m3 to bring outwater volume plan outside of work time (14 hours) and analternative pump was add 1 unit of recommendation pump with the same type such as Mitshubisi6D16 gravel pump (engine) with a pump capacity of 154.8 m3/h, but the actual pump was still beingused so that with the use of two unit pump acquired total pump capacity was 241.2 m3/h with thelifetime of pumping was 9 hours to remove the water 2172.588 m3/per day.